ANALISIS MOTIVASI, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PT. SKY AVIATION DISTRIC MAKASSAR - Arfiyani, Arfiyani; Putro, Guntur Suryo (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2020)
The element of need is an internal condition that causes results to appear attractive. An unsatisfied need creates a tension that stimulates the impulse within the individual. Employee coaching is one of the priority assets of the company. This study uses a Partial Least Square (PLS) approach. PLS is a component or variant based Structural Equation Modeling (SEM) equation model, the result is the residual variance of the dependent variable.The samples proposed in this study were 35 respondents to test the operational hypothesis by using the t test statistic, at the level of a = 10%, so that the resulting decision: Rejecting Ho if t> t table, means that the model is significant and there is a relationship effect. Accept Ho if t count <t table, it means that the model is significant and there is no relationship. Rejecting Ho if t count> t table, it means that the model is significant and there is an effect. Receiving Ho if t count <t table, it means that the model is significant and there is no relationship effect.Work motivation variables, work environment and work culture have an influence of 76.1% (R square value of 0.761%) so there are still 21.8% of other variables that influence job satisfaction apart from the variables examined in this study.Keywords: Motivation, Work Environment, Organizational Culture and Employee Job Satisfaction